Healthy lifestyle campaign as social intervention mechanism to youth well-being: a case study on fit Malaysia social media campaign / Suffian Hadi Ayub - Ayub, Suffian Hadi (2020)
The purpose of this study is to explore the effectiveness of healthy lifestyle campaign on social media and its impact on youth well-being in Malaysia. FIT Malaysia was introduced by Ministry of Youth and Sports (MOYS) to transform Malaysia to a sporting nation. It serves as a catalyst for Malaysians especially youth to understand the importance of healthy lifestyle. Since youth is the future of the country and represents 40% of total Malaysia population, FIT Malaysia initiated various integrated marketing communication plans to ensure its programmes such as running, cycling, and fitness activities reach the public nationwide. A report by Malaysia Communication and Multimedia Commission (MCMC) stated that youth spent more time online, and as the most effective tools to communicate the importance of healthy lifestyle would be through social media bandwagon. Additionally, youth also has been found to be more attracted to web 2.0 since it allowed for user generated content and it provide better engagement between FIT Malaysia. The study embarked to explore the processes undertaken by FIT Malaysia to develop healthy lifestyle campaign on its social media platforms through the identification of the competency capabilities and social media characteristics itself. The study employed qualitative methodology to explore the perceived impact of FIT Malaysia to youth through in-depth interview with five policy makers and officials from MOYS as well as FIT Malaysia secretariat. Qualitative content analysis was also used to investigate FIT Malaysia’s official Facebook (FB) and twitter page using the images, texts, and postings. To understand further youth’s perception on FIT Malaysia campaign, two focus group discussions were conducted with youth in Klang Valley to ascertain the perception of FIT Malaysia contents used on FB and twitter. With social marketing theoretical framework, these three approaches went through triangulation method to confirm the three aspects namely sender, message, and receiver involved in the delivery of the healthy lifestyle campaign. It was then interlaced to capture the essence of social intervention, while uses and gratification theory was employed to draw parallel that served as intervening mechanism between sender and receivers. The analysis discovered that while FIT Malaysia employed a systematic posting and engaged external consultants to strengthen its social media presence, MOYS must be willing to extend FIT Malaysia’s financial capabilities to advance its manpower capabilities through proper training and recruitment for skill developments as well as the number of officials administering the social media platforms. This is crucial as social media engagement is vital to the livelihood, expansion, and visibilities of FIT Malaysia. To this end, FIT Malaysia through its social media administrator would be able to successfully immerse on conversational aspect of social media. This would gauge youth participation while cognitively allow for social intervention through active virtual engagement in creating awareness and education which is a pre-requisite to modification of behaviour where the aspiration to become a sporting nation could be realised.